The Influence of Audio Visual (Video) Imagination on Hospitalization Stress in Hemodialysis Patients at the Siti Khadijah Islamic Hospital, Palembang - Serli Wulan Safitri; Selamat Parmin (MultiTech Publisher, 2023)
Kupriyanov and Zhdanov (2014) stated that current stress is an attribute of modern life. The aim of this research is to determine the effect of imagination using audio-visual (video) on hospitalization stress in hemodialysis patients at the Siti Khadijah Islamic Hospital, Palembang. The research design used was pre-experiment with a one group pre-post test design approach. The sample consisted of 20 people. Sampling was carried out using accidental sampling technique. Then the data was analyzed using the nonparametric Marginal Homogeneity test. The results of data analysis using the non-parametric Marginal Homogeneity test showed that there was a significant effect of providing audio-visual (video) imagination therapy before and after on stress in hemodialysis patients with a p value of 0.001 < α (0.05).